Melanocyte count on leukotrichia in vitiligo using S100 protein immunohistochemistry before and after phototherapy: A case report - Wardhani, Putri Hendria; Prakoeswa, Cita Rosita Sigit; Listiawan, M. Yulianto; Astari, Linda; Zulkarnain, Iskandar; Murtiastutik, Dwi; Setyaningrum, Trisniartami (Journal of Pakistan Association of Dermatologists, 2020)
Vitiligo is the most common depigmentation disease with complex pathogenesis that is not well understood and therapeutic outcomes are often unsatisfactory. Leukotrichia in vitiligo is often associated with poor prognosis for vitiligo treatment. Until now narrowband ultraviolet B (NB-UVB) is considered the most effective and safe treatment for vitiligo. Evaluation of therapy by looking at the amount of melanocytes that can be seen with S100 protein immunohistochemistry will become more objective and accurate. Melanocyte count in four non segmental vitiligo patient with leukotrichia were evaluated. The patient was given only NB-UVB therapy twice a week for eight times. Skin biopsy was done before and after therapies using immunohistochemistry staining. The number of S100 protein in vitiligo patients with leukotrichia after NB-UVB therapy increased. Leukotrichia is a poor indicator for treatment response in vitiligo, but this case report showed that leucotrichia did not contribute to the lack of response upon medical treatment.Â